2001
DOI: 10.7901/2169-3358-2001-1-309
|View full text |Cite
|
Sign up to set email alerts
|

Microcosm Study of Effect of Different Nutrient Addition on Bioremediation of Fuel Oil No. 2 in Soil from Nova Scotia Coastal Marshes

Abstract: Biostimulation has been shown to be an effective tool for the treatment of oil spills in medium to low-energy marine environments. Little information is available on the bioremediation of oil spills in low-energy coastal wetlands. Most of the previous laboratory studies have been carried out under total flooding conditions. In this study, a tidal salt marsh was simulated in laboratory microcosms. The study was carried out in glass columns filled to a depth of 10 cm with sediment. Each microcosm was operated on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, bacterial respiration and organic mineralization were significantly reduced as the salinity increased. Garcia-Blanco et al (2001) in a microcosm study indicated that the lack of oxygen may limit the hydrocarbon biodegradation in a simulated tidal salt marsh environment. Mille et al (Mille et al 1991) reported that crude oil biodegradation by a mixed aerobic bacterial community isolated from a marine sediment was enhanced to a maximum NaCl concentration of 0.4 mol L −1 and then decreased for the higher concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, bacterial respiration and organic mineralization were significantly reduced as the salinity increased. Garcia-Blanco et al (2001) in a microcosm study indicated that the lack of oxygen may limit the hydrocarbon biodegradation in a simulated tidal salt marsh environment. Mille et al (Mille et al 1991) reported that crude oil biodegradation by a mixed aerobic bacterial community isolated from a marine sediment was enhanced to a maximum NaCl concentration of 0.4 mol L −1 and then decreased for the higher concentrations.…”
Section: Introductionmentioning
confidence: 99%